2022
DOI: 10.15244/pjoes/147187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Intercropping Methods on Soil Organic Carbon and Aggregate Stability in Sugarcane Field

Abstract: In order to maintain soil stability, improve soil productivity and optimize planting patterns, the distribution characteristics of soil aggregates in sugarcane fields under different intercropping methods were studied. We investigated the differences in organic carbon content of different particle size aggregates and the effects of intercropping on soil organic carbon, aggregates stability, sugarcane water content and nutrients content. The results showed that intercropping could effectively improve soil physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Generally, intercropping could affect microbial diversity and ecosystem functions via its effect in soil properties ( Nyawade et al, 2019b ; Curtright and Tiemann, 2021 ). Intercropping can affect the content and distribution of soil aggregates to improve soil physicochemical properties ( Hu et al, 2022 ). For instance, soil macro-and microaggregates are higher in maize/faba bean or maize/pigeon pea intercropping systems than in the monocropping system of maize ( Garland et al, 2016 ; Tian et al, 2019 ), which could further increase soil stability ( Tong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, intercropping could affect microbial diversity and ecosystem functions via its effect in soil properties ( Nyawade et al, 2019b ; Curtright and Tiemann, 2021 ). Intercropping can affect the content and distribution of soil aggregates to improve soil physicochemical properties ( Hu et al, 2022 ). For instance, soil macro-and microaggregates are higher in maize/faba bean or maize/pigeon pea intercropping systems than in the monocropping system of maize ( Garland et al, 2016 ; Tian et al, 2019 ), which could further increase soil stability ( Tong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Correlation between physical and chemical properties, carbon composition, enzyme activity and mineralization of (A) OBC-Mg and (B) OBC-Mg. Hu et al 10.3389/fmicb.2023.1109272 Frontiers in Microbiology 14 frontiersin.org the MBC was significantly and positively correlated with the cumulative mineralization of organic carbon, indicating that the mineralization of soil organic carbon also affects the MBC. Soil dissolved organic carbon (DOC) is the most active component of SOC and an important source of organic carbon and an important indicator of soil microbial effectiveness (Hu et al, 2022). In this study, application of OBC and OBC-Mg to citrus orchard soil increased DOC content and showed an overall decreasing trend with increasing incubation time.…”
Section: Effect Of Biochar On Different Carbon Fractions In Citrus Or...mentioning
confidence: 79%
“…In contrast to the moso bamboo monoculture, intercropping induced an increase in soil organic carbon, total N, and P in the topsoil, which was verified in multiple agroforestry systems [46,47]. Several studies indicated that dead plant matter and root exudates were important sources of soil organic matter; the presence of more dead matter and roots in the intercropping systems increased the inputs of organic matter into the soil [48,49].…”
Section: Effects Of Intercropping On Soil Propertiesmentioning
confidence: 90%